Optimal Design Planning for Minor Irrigation Structures in Jalpaiguri District of West Bengal - Singh, R K; Mal, B K (Journal of Agricultural Engineering, 2007)
A study was undertaken to assess and utilize the water resources in nine administrative blocks of Jalpaiguri district in West Bengal by allocating the land and water effectively. Gated concrete structures were designed on the basis of peak period discharge to harness and use the surface water effectively. Non-scouring canals were also designed on the basis of lean (Dry) period discharge. Hydrologic, hydraulic and structural designs of the structures were made using relevant information on topography, soil, rainfall, HFL etc. The dry period discharge in different streams varied from 0.03 to 3.756 mÂ³/s, which can be used as minor irrigation sources by constructing diversion structures and canals. The surface runoff in different streams varied from 21.24 to 111.08 Mha-mm. Part of water can be stored for irrigation in the dry period. Gated structures designed for water diversion will be helpful in combating the siltation problem.